Optically active Babinet planar metamaterial film for terahertz polarization manipulation. Issue 5 (10th June 2013) - Zalkovskij, Maksim; Malureanu, Radu; Kremers, Christian; Chigrin, Dmitry N.; Novitsky, Andey; Zhukovsky, Sergei; Tang, Peter T.; Jepsen, Peter U.; Lavrinenko, Andrei V.
<x xml:space="preserve">Abstract</x> A planar Babinet‐inverted dimer metamaterial possessing strong optical activity is proposed and characterized. An original fabrication method to produce large area (up to several cm2) freely suspended flexible metallic membranes is implemented to fabricate the metamaterial. Its optical properties are characterized by terahertz time‐domain spectroscopy, revealing anisotropic transmission with high optical activity. A simple coupled resonator model is applied to explain the principal optical features of the dimers, with predictive power of positions and number of resonances through a parametrical model. The model is validated for correct polarization‐dependent quantitative results on the optical activity in transmission spectra. The fabrication method presented in this work as well as the slit dimer design has great potential for exploitation in terahertz optics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>